Características morfogênicas, estruturais e produtivas de acessos de capim-buffel - Moreira, José Armando de Sousa (2013)
The aim of this study was to evaluate the morphogenesis, structural and productive access of buffel grass (Cenchrus ciliaris L.). The experiment was conducted at the Department of Technology and Social Sciences (DTCS) University of Bahia (UNEB) in Juazeiro-BA, from November 2008 to January 2009. The experimental design was completely randomized with six accessions of buffel grass (Tanzania, Pusa Giant, Aridus, Buchuma, Iran and Biloela) and five replicates, totaling 30 experimental units. The accesses differ statistically (P <0.05) in most variables, especially in morphogenetic and structural variables. However, these differences did not influence morphogenetic and structural parameters productive. It was observed that the buffel grass provides a mean rate of appearance of one leef every four days in each tiller, with a lifetime of leef 17 days, keeping ten per tiller